Dick Bierman letter to Nicholas S. Halmi regarding winter bird sightings, February 6, 1979 - Bierman, Dicket al (1979)
Letter from Dick Bierman to Nicholas S. Halmi regarding winter bird sightings, February 6, 1979. Sightings of Pileated Woodpecker and Bohemian Waxwings are underlined in red. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1978-1979. Epson - sheet feed/flatbed